Aiming point trajectory as an assessment parameter of shooting performance - Zanevskyy, I.; Korostylova, Y.; Mykhaylov, V. (Human Movement, 2012)
Purpose. The purpose of this study was to elaborate on the scientific methodology for providing an assessment of air-pistol shooters` aiming stability by (i) substantiating the parameters of aiming stability, (ii) specifying the quantitative evaluation methods in using an optoelectronic target, (iii) evaluating the reliability of tests determining aiming stability, and (iv) developing a methodology for creating individual and group parameters of aiming stability. Methods. The aiming trajectories of 95 airpistol shooters, each of whom fired 60 shots using a SCATT optoelectronic simulator, were calculated to develop individual and group aiming stability parameters. Research methods included an optoelectronic registration of movement, research on top air-pistol shooters` sports results, mathematical modelling, variation statistics, cluster analysis, two-way ANOVA with data correlation and reliability theory tests. Results. It was found that an average aiming point trajectory on the SCATT optoelectronic target measured one second before a shot could be accepted as an assessment parameter of aiming stability, as it is one of the basic parameters of technical preparation and its position is not influenced by the ballistic characteristics of the pistol and pellets (? = 0.944). Conclusions. The parameters of aiming stability in air-pistol shooting were developed using a modification of the clustering method. This allows for the identification of weak points in the structure and organization of shooters` training and for adjustment of the training process.